Top sources of dietary sodium from birth to age 24 mo, United States, 2003–2010. Issue 5 (11th March 2015) - Maalouf, Joyce; Cogswell, Mary E; Yuan, Keming; Martin, Carrie; Gunn, Janelle P; Pehrsson, Pamela; Merritt, Robert; Bowman, Barbara
ABSTRACT: Background: Sodium intake is high in US children. Data are limited on the dietary sources of sodium, especially from birth to age 24 mo. Objective: We identified top sources of dietary sodium in US children from birth to age 24 mo. Design: Data from the NHANES 2003–2010 were used to examine food sources of sodium (population proportions and mean intakes) in 778 participants aged 0–5.9 mo, 914 participants aged 6–11.9 mo, and 1219 participants aged 12–23.9 mo by sociodemographic characteristics. Results: Overall, mean dietary sodium intake was low in 0–5.9-mo-old children, and the top contributors were formula (71.7%), human milk (22.9%), and commercial baby foods (2.2%). In infants aged 6–11.9 mo, the top 5 contributors were formula (26.7%), commercial baby foods (8.8%), soups (6.1%), pasta mixed dishes (4.0%), and human milk (3.9%). In children aged 12–23.9 mo, the top contributors were milk (12.2%), soups (5.4%), cheese (5.2%), pasta mixed dishes (5.1%), and frankfurters and sausages (4.6%). Despite significant variation in top food categories across racial/ethnic groups, commercial baby foods were a top food contributor in children aged 6–11.9 mo, and frankfurters and sausages were a top food contributor in children aged 12–23.9 mo. The top 5 food categories that contributed to sodium intake also differed by sex. Most of the sodium consumed (83–90%) came from store foods (e.g., from the supermarket). In children aged 12–23.9 mo, 9% of sodium consumed came from restaurant foods, and 4% of sodium came from childcare center foods. Conclusions: The vast majority of sodium consumed comes from foods other than infant formula or human milk after the age of 6 mo. Although the majority of sodium intake was from store foods, after age 12 mo, restaurant foods contribute significantly to intake. Reducing the sodium content in these settings would reduce sodium intake in the youngest consumers.